Islamic Mass Organizations Figures’ Views on Ulī al-amr: Implications for Indonesian Democracy and Compliance with The Government - Busyro, Busyro; Imran, Maizul; Zainuddin, Zainuddin; Asmara, Musda; Ismail, Ismail (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
Diverse views among Indonesian Islamic mass organizations’ figures over the existence of the Republic of Indonesia and obedience issue to the government became a topic of discussion, particularly when the government’s decision about religious issues differs from that of organization. This study aimed to find out in depth about views on ulī al-amr among figures from some Indonesian Islamic mass organizations and the issue of obedience to it within a democratic state system. This research is descriptive qualitative, using focused interviews in data collection. It is inductive in nature, which aims at developing process-oriented theories or values and data. The findings of the research showed that the representative figures recognize the Indonesian government as ulī al-amr, including ahlu al-bayt Indonesia, who prefer not to use the term because it is related to the requirement of chastity (‘ismah). This recognition implied an obligation to obey the Indonesian government, even though it is run by a democratic system, not Islam. As for matters related to specific religious regulations, such as determining the beginning of Ramadan, Shawwal, etc., differences from the government are not deemed as deviating from ulī al-amr, considering the democratic nature of the state, in which it provides opportunities to be diverse and recognizes those differences.